Karakteristik Struktur dan Listrik Film Tipis GaN yang Ditumbuhkan di atas Substrat Si(111) dengan Metode Plasma Assisted-Metalorganic Chemical Vapor Deposition (PA-MOCVD) - Heri Sutanto; Agus Subagio; Edi Supriyanto; Pepen Arifin; Sukirno Sukirno; Maman Budiman; Mohamad Barmawi (Institut Teknologi Bandung, 2006)
Gallium nitride (GaN) thin films have been grown on Si(111) substrate by PA-MOCVD method, with trimethylgallium (TMGa) and radical nitrogen resulted by plasma of nitrogen gas as a source of Ga and N respectively. The growth was performed at 675 Â°C; 0.4 torr; 90 sccm and 0.08-0.12 sccm of substrate temperature, reactor pressure, gas flow of nitrogen and TMGa, respectively. The grown polycrystalline GaN thin films have hexagonal structure and n-type semiconductor. The growth rate of the grown thin films increased with increasing gas flow of TMGa. The Hall mobility value of films is still low due to the presence of O and C impurities. The highest value of mobility was found to be 64.88 cm2/V.s with 5.47 x 1018 cm-3 of carrier concentration.